1998
DOI: 10.1200/jco.1998.16.1.133
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counseling and testing for breast-ovarian cancer susceptibility: what do women want?

Abstract: When feasible, the optimal approach may be for oncologists to work with genetic counselors to provide pretest education and medical recommendations. Elicitation of patients' preferences may be useful to determine the level of counseling services needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…tremely" [5]). Twenty-two percent (21.8%) of the men were "extremely" concerned about their family history of cancer, and only 6.4% indicated they were "not at all" concerned.…”
Section: Genetic Services For Menmentioning
confidence: 99%
See 3 more Smart Citations
“…tremely" [5]). Twenty-two percent (21.8%) of the men were "extremely" concerned about their family history of cancer, and only 6.4% indicated they were "not at all" concerned.…”
Section: Genetic Services For Menmentioning
confidence: 99%
“…Twenty-two percent (21.8%) of the men were "extremely" concerned about their family history of cancer, and only 6.4% indicated they were "not at all" concerned. Respondents thought the amount of information they had received about their prostate cancer risk was less than enough with a mean rating for the amount of information of 2.15 (SD ϭ 0.92, range: "not enough" [1], "enough" [3], "too much" [5]). A total of 59.6% of respondents indicated they had received less than enough information about this risk.…”
Section: Genetic Services For Menmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have examined levels of breast cancer genetics knowledge among women with a family history of breast cancer (Lerman et al, 1996Hughes et al, 1997;Wonderlick and Fine, 1997;Cull et al, 1998;Bluman et al, 1999;Donovan and Tucker, 2000) have found wide variation in knowledge about many facets of genetic testing, including the cancer risks associated with different genes and different mutations and the effectiveness of interventions, for example screening, chemoprevention, or surgery for reducing risk (Geller et al, 1997;Audrain et al, 1998;Bluman et al, 1999).…”
mentioning
confidence: 99%